СRITICAL MEDIA DISCOURSE ANALYSIS: POLISH EUCATION IN BELARUS (ON THE MATERIAL OF WEEKLY “GŁOS ZNAD NIEMNA NA UCHODŹSTWIE”) - Жак, Вальдемар (Current Issues of Foreign Philology, 2021)
The paper considers one of the most powerful and well-developed directions of modern discourse analysis – the critical discourse analysis, its methods, main principles and their application to research, as well as proposes method of analysis discourse concerning education and Polish school system in Belarus which took place in the period 2014-2016 in “Głos znad Niemna na uchodźstwie” weekly. “Discourse” being the matter of interest of different sciences is quite a disputable phenomenon nowadays. Due to the attempts of the scholars the theory of discourse is being developed as a separate sphere of science thus becoming a core in the process of modern science integration and enabling a deeper and wider study of the phenomenon under consideration and finding its general and peculiar characteristics. Based on the critical discourse analysis, the article explores relevant events, main themes and contexts in which the Polish people living are represented as actors, as well as speech and cognitive techniques used to cover the diaspora topics. The situation of Poles as Polish people living abroad in the contemporary Belarus seems to be complicated. On one hand, they occur to be a significant percentage of the society in Belarus, but on the other hand, the significant part of them has a difficulty to preserve Polish identity. Polish media in Belarus plays a vital role in the process of creation and development of national consciousness. It proves to be the essential source of cognition. “Głos znad Niemna na uchodźstwie” weekly issued as the press organ of the Union of Poles in Belarus has been playing such a vital role for years. The critical discourse analysis has proved to be of special helpfulness, the analysis in relation to the ethnic and national minority problematic aspects. One should highlight the fact that the public discourse is used both for the creation and reinforcement of the national identity. One has made five analysis of papers of choice concerning the education and Polish school system in Belarus in “Głos znad Niemna na uchodźstwie weekly, the analysis which were very helpful as for which topic issues concerning Polish education in Belarus are highlighted in the press; what the discourse construction is, types of used vocabulary and structures; which results for behaviour and the way of readers thinking are obtained by reading texts printed in the weekly.